Application of Aloevera Compress Therapy in Nursing Care in Children with Hyperthermia - Pusmawati, Tiana; Cahyaningrum, Etika Dewi (PROMOTOR, 2024)
Fever is a condition of increasing body temperature more than 37.5°C where this is one of the body's responses to symptoms of disease that are usually caused by infections, the effects of drugs, and autoimmune diseases. Reducing or controlling fever in children can be done in various ways, including pharmacologically and physically (non-pharmacological) namely aloevera compresses. The purpose of aloevera compress therapy is used to reduce body temperature in children who experience hyperthermia with a body temperature of 37.5°C - 38.5°C.  The method in this study uses a descriptive method with a nursing care process approach. The instruments used are SOPs for the application of aloevera compress therapy, thermometers, and observation sheets. This study was conducted from April 22 to April 24, 2024.  Based on the results of studies, diagnoses, nursing care plans, implementation and evaluation as well as the application of evidence-based nursing, it was found that when the application of aloevera compress intervention on An. F with hyperthermia in the inpatient room of Aster Hospital, Prof. Dr. Margono Soekarjo Purwokerto, that after the intervention was given, the body temperature decreased, before being given aloevera compresses, the child's body temperature was 38.2 ° C, while after being given aloevera compresses, the child's body temperature became 37.1 ° C.  Results of evaluation of the application of aloevera compresses in     An. F within 3 days shows the effect of giving aloevera compress therapy on reducing children's body temperature.